Emerging CNS Viral Infections - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
In a 2-part review, a neuroinfectious disease specialist at the University of Colorado Denver Health Sciences Center and Veterans Medical Center describes emerging viral infections as diseases that infect new hosts, spread into new geographic areas, alter their pathogenesis, or are caused by agents not recognized as pathogenic.